Long-read sequencing of oropharyngeal squamous cell carcinoma tumors reveal diverse patterns of high-risk Human Papillomavirus integration - Gauthier, Marc-Andre; Kadam, Adway; Leveque, Gary; Golabi, Nahid; Zeitouni, Anthony; Richardson, Keith; Mascarella, Marco; Sadeghi, Nader; Loganathan, Sampath Kumar (Frontiers in Oncology, 2023)
In North America and in most European countries, Human Papillomavirus (HPV) is responsible for over 70% of oropharyngeal squamous cell carcinomas. The burden of OPSCC, in highincome countries, has been steadily increasing over the past 20 years. As a result, in the USA and in the UK, the burden of HPV-related oropharyngeal squamous cell carcinoma in men has now surpassed that of cervical cancer in women. However, the oncogenic impact of high-risk HPV integration in oropharyngeal squamous cell carcinomas hasn't been extensively studied. The present study aimed to explore the patterns of HPV integration in oropharyngeal squamous cell carcinomas and to assess the feasibility and reliability of long-read sequencing technology in detecting viral integration events in oropharyngeal head and neck cancers. Methods: A cohort of eight HPV-positive OPSCC pre-treatment patient tumors (four males and four females), were selected. All patients received a p16 INK4A positive OPSCC diagnosis and were treated at the McGill University Health Centre, a quaternary center in Montreal. A minimum of 20mg of tumor tissue was used for DNA extraction. Extracted DNA was subjected to Nanopore long-read sequencing to detect and analyze for the presence of high-risk HPV sequences. PCR and Sanger sequencing experiments were performed to confirm Nanopore long-read sequencing readings.Results: Nanopore long-read sequencing showed that seven out of eight patient samples displayed either integrated or episomal high-risk HPV sequences. Out of these seven samples, four displayed verifiable integration events upon bioinformatic analysis. Integration confirmation experiments were designed for all four samples using PCR-based methods. Sanger sequencing was also performed. Four distinct HPV integration patterns were identified: concatemer chromosomal integration in a single chromosome, bi-chromosomal concatemer integration, single chromosome complete integration and bi-chromosomal complete integration. HPV concatemer integration also proved more common than full HPV integration events.Long-read sequencing technologies can be effectively used to assess HPV integration patterns in OPSCC tumors. Clinically, more research should be conducted on the prognostication value of high-risk HPV integration in OPSCC tumors using long-read sequencing technology.